(3bVGjG ESdGejI eYGUQI aj GdfbhO hGdHfhc hGdJehjds - (3YHO GdQMeGf jSQi(B, (3CMeOs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2001)
(3GdfbhO(B-(3GdaGFOI hJWHjbgG eY GdQHG(B-(3ehba abgGA GdESdGe efGdaGFOI(B-(3YQV hJMdjd dBQGA GdGbJUGOjjf GdESdGejjf aj GdQHW GdbjGSj(B-(3GdQHW GdbjGSj ddCLhQ HGdeSJhi GdYGe ddCSYGQ(B-(3GdHfhc GdESdGejI(B-(3GdHfhc GdJbdjOjI hGdJMhd Edi GdEdJRGe HGdTQjYI GdESdGejI(B-(3GdJehjd HGdYLRs
(3HHdjhZQGajG(B: (3U(B.482s
Keywords: (3GdEbJUGO GdESdGejs; (3GdHfhcs; (3GdfbhOs